Using mHealth tools to improve access, coverage and treatment of uninsured people with high cardiovascular disease risk in Argentina: a study protocol for a pragmatic cluster randomised trial. Issue 3 (2nd June 2018) - Abrahams-Gessel, Shafika; Beratarrechea, Andrea; Irazola, Vilma; Gutierrez, Laura; Moyano, Daniela; Fernandez, Ariel; Ciganda, Alvaro; Celis, Leo Anthony; Winkler, Eric; Rubinstein, Adolfo; Gaziano, Thomas A
Abstract : Introduction: Cardiovascular disease (CVD) accounts for approximately one-third of Argentina's deaths. Despite government provision of free primary care health services to the uninsured population, with a focus on non-communicable diseases, screening and management of those with high CVD risk at primary care clinics (PCCs) remain low. Methods and analysis: This pragmatic cluster randomised trial will take place in two provinces of Argentina and will recruit 740 participants. Eight PCCs will be randomised to either the intervention or current practice arm. Community health workers (CHWs) in the intervention arm will be trained to use a set of integrated mHealth tools (a validated risk screening tool mobile application; electronic scheduling system using wireless access to PCCs; and educational text messages) to screen for CVD and to schedule appointments with primary care providers for persons with high CVD risk (≥10%). The primary aims of this study are to determine if the use of mHealth tools will (1) increase attendance of first appointments scheduled by CHWs for persons determined to have high risk for CVD during screening and, (2) lead to an increase in follow-up visits at PCCs by high risk patients. Secondary outcomes include assessing the proportion of high-risk patients receiving appropriate medications and a cost-effective analysis of the intervention. Ethics and dissemination: This study has been approved by the Institutional Review Boards at Partners/Brigham and Women's Hospital (USA) and the Hospital Italiano de Buenos Aires (Argentina). The open-source software for the mHealth tools will be made publicly available at the end of the study. Trial registration number: NCT02913339 .